Pengaruh Kepemimpinan Egaliter, Tanggung Jawab, dan Disiplin Kerja terhadap Kinerja Guru dengan Moderasi Pemberdayaan Psikologis Lembaga TPQ Kecamatan Bengkong - Mutiara Rizkika Sibarani; Yandra Rivaldo; Jeffi Mutiara (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
This study aims to analyze the influence of egalitarian leadership, responsibility, and teacher work discipline on teacher performance with the moderation of psychological empowerment at Qur'anic Education Institutions (TPQ) in Bengkong District, Batam. A quantitative approach was employed using Structural Equation Modeling Partial Least Square (PLS-SEM) via SmartPLS software. The population comprised all TPQ teachers in Bengkong District, with a sample of 84 teachers selected by proportionate random sampling. Teacher performance was assessed by TPQ principals to enhance objectivity. Results revealed that work discipline is the strongest predictor of teacher performance (coefficient 0.454; T=4.370; p=0.000), followed by responsibility (coefficient 0.254; T=2.557; p=0.011), and psychological empowerment (coefficient 0.232; T=1.992; p=0.047). Egalitarian leadership showed no significant direct effect (p=0.720). Psychological empowerment did not significantly moderate the relationships between the three independent variables and teacher performance. The model demonstrated very high predictive power with R Square of 0.929. This study implies that strengthening work discipline and responsibility are priority strategies for improving TPQ teacher performance.